2019
DOI: 10.1002/cpt.1352
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Therapy Drugs in China, Japan, and the United States: Pharmacokinetic Characteristics, Dose Regimens, and Development Strategies

Abstract: The oncology targeted therapy and immunotherapy drugs approved in the United States, Japan, and China were reviewed. No clinically meaningful difference in pharmacokinetic characteristics or in dose regimens was observed among Western, Japanese, and Chinese populations. Integrated global development strategies in China and Japan are proposed, including potential waiver of the phase I pharmacokinetic/ tolerability studies in Asian patients, based on ethnic sensitivity assessment for new oncology drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…This was consistent with previous reports. 6 , 7 , 8 , 9 We also echo the previous reports 2 , 3 , 10 that PK of mAbs are similar in Japanese and non‐Japanese. In general, mAbs are not widely distributed to organs/tissues, and elimination is not related to the expression level and activity of drug‐metabolizing enzymes and transporters, 2 characteristics associated with low ethnic sensitivity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was consistent with previous reports. 6 , 7 , 8 , 9 We also echo the previous reports 2 , 3 , 10 that PK of mAbs are similar in Japanese and non‐Japanese. In general, mAbs are not widely distributed to organs/tissues, and elimination is not related to the expression level and activity of drug‐metabolizing enzymes and transporters, 2 characteristics associated with low ethnic sensitivity.…”
Section: Discussionsupporting
confidence: 89%
“…However, the general findings and proposals are consistent with those previously published. 2,3,7,9,10 The authors hope that this report will lead to further discussion on this topic with other pharmaceutical companies, academia, and regulatory agencies.…”
Section: Discussionmentioning
confidence: 95%
“…10,11 Of note, 10 mg/kg every 2 weeks was not administered to Chinese patients in this study. However, our previous PPK analyses demonstrated that race (Chinese or Asian versus non-Asian) was not a clinically meaningful covariate for nivolumab exposures, 19 which is consistent with observations of other immuno-oncology drugs, 27 and there were also similar distributions of PK parameters across different races. 28 Even in studies in which flat dosing in an Asian population may be associated with higher exposure, there may not be a significant impact on safety.…”
Section: Discussionsupporting
confidence: 72%
“…Across global regions, bevacizumab dosing is based on body weight, and atezolizumab uses flat dosing that does not require adjustments to account for regional body size differences. The similarity in dosing regimens for Western versus Asian regions is also seen with other mAbs; a survey of 22 biologics (predominantly mAbs) for oncology use approved in Japan, China, and the USA prior to 2018 showed no differences between dosing regimens used in Asian and Western populations [60].…”
Section: Discussionmentioning
confidence: 97%